Prokaryotic organelle mitochondria drive tumorigenesis: “the original sin” - Wang, Chaoyi; Luo, Ming; Zhou, Jinhui; Zhang, Qihao; Ji, Xiawei; He, Jiayao; Wang, Lingfei; Huang, Yingpeng; Xue, Xiangyang; Wang, Fangyan (Frontiers in Oncology, 2026)
Mitochondria preserve bacterial traits because of their endosymbiotic origin, and their alterations in cancer cells reflect these prokaryotic-like traits. One such trait is the Warburg effect, wherein tumor cells rely primarily on aerobic glycolysis instead of oxidative phosphorylation. Cancer cells also exhibit metabolic abnormalities, such as an uncoupled electron transport chain and a truncated tricarboxylic acid (TCA) cycle, potentially generating additional energy. Intermediates from the disrupted TCA cycle can regulate key genes involved in cell differentiation, apoptosis, and tumor suppression while promoting aerobic glycolysis, angiogenesis, and resistance to cell death. Mitochondria-related gene mutations, particularly in D-loop and TCA-related enzymes, have been identified as key drivers of prokaryotic transformation in diverse cancers. Furthermore, the metabolic activity of cancer mitochondria results in the production of essential biosynthetic precursors for nucleotide synthesis and lipid synthesis, supporting tumor growth. Mitochondria also contribute to tumorigenesis by promoting inflammation and iron metabolism disorders. Mitochondrial dysfunctions have raised interest in the use of mitochondria-targeted anticancer strategies as possible cancer treatments, although their clinical application requires further investigation.